PEMAHAMAN ORANG TUA TERHADAP PENDIDIKAN SEKS ANAK USIA DINI DI KECAMATAN SEKADAU HILIR - Azis, Nabila Alvionita; Yuniarni, Desni; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to describe the understing of parents of early childhood sex education at district Sekadau Hilir. The research method used is qualitative with descriptive research type. The subjects of this study are parents at district Sekadau Hilir who has early childhood. The location of this research is at district Sekadau Hilir. The data collection technique of this research was interview and documentation techniques. The data collection tool uses iterview guidelines and documentation. The results of this study are parents understanding of early childhood sex education in the district Sekadau Hilir, parents already have knowledge of early childhood sex education. Parents understand the recognition of the sex of women and men in early childhood, explain the differences in the body of man and women, introduce human sexual organs, protect children from sexual cirmes and know cases of sexual crimes that occur. The implication is that parents already understand early childhood sex education, but there are still some parents who do not fully undersatand early childhood sex education.Â Keywords: Early Childhood, Parental Understanding, Sex EducationÂ